2005
DOI: 10.1128/jb.187.17.6119-6127.2005
|View full text |Cite
|
Sign up to set email alerts
|

ExploringLactobacillus plantarumGenome Diversity by Using Microarrays

Abstract: Lactobacillus plantarum is a versatile and flexible species that is encountered in a variety of niches and can utilize a broad range of fermentable carbon sources. To assess if this versatility is linked to a variable gene pool, microarrays containing a subset of small genomic fragments of L. plantarum strain WCFS1 were used to perform stringent genotyping of 20 strains of L. plantarum from various sources. The gene categories with the most genes conserved in all strains were those involved in biosynthesis or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
219
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(230 citation statements)
references
References 50 publications
10
219
0
1
Order By: Relevance
“…While the role of the S-linked HexNAc is enigmatic, it is interesting to consider the evolutionary and ecological consequences of 'baiting' bacteriocins with monosaccharides that are components of cell wall polymers and/or substrates for specific phosphotransferase system (PTS) transporters. The latter are numerous in L. plantarum [29], and transmembrane subunits of mannose PTS transporters are known receptors for class II bacteriocins [30]. Further, the S-glycosidic linkage could be relatively resistant to cleavage by extracellular and cell envelope glycosidases and transglycosylases, a strategy akin to incorporating D-amino acids into antimicrobial peptides to minimise proteolysis [31].…”
Section: Discusssionmentioning
confidence: 99%
“…While the role of the S-linked HexNAc is enigmatic, it is interesting to consider the evolutionary and ecological consequences of 'baiting' bacteriocins with monosaccharides that are components of cell wall polymers and/or substrates for specific phosphotransferase system (PTS) transporters. The latter are numerous in L. plantarum [29], and transmembrane subunits of mannose PTS transporters are known receptors for class II bacteriocins [30]. Further, the S-glycosidic linkage could be relatively resistant to cleavage by extracellular and cell envelope glycosidases and transglycosylases, a strategy akin to incorporating D-amino acids into antimicrobial peptides to minimise proteolysis [31].…”
Section: Discusssionmentioning
confidence: 99%
“…Lactobacillus plantarum has been found in a wide range of natural and artificial fermentation processes, in particular in plant-derived matrices [58]. It is a very versatile microorganism that produces large amount of lactic acid and causes acidification of the fermentation medium [59], thus favouring the hydrogen producing microorganisms versus the methanogenic ones.…”
Section: Staphylococcusmentioning
confidence: 99%
“…These C11 plantaricins showed activity against closely related species (Anderssen et al, 1998), which can be found in the same ecological niches as L. plantarum strains WCFS1 and C11 . However, some strain-specific differences in plantaricin activity and target specificity might be expected for various L. plantarum strains, considering the differences in pln gene composition and sequence variations identified in the pln operons of strains WCFS1, C11 and NC8 (Maldonado et al, 2004;Molenaar et al, 2005).…”
Section: Plantaricin Tcs Pln (Lp_0415 To Lp_0418)mentioning
confidence: 99%